ANALISIS STRATEGI BAURAN PEMASARAN PADA TOKO BUNDA CAKE & BAKERY BUKITTINGGI MENURUT PERSPEKTIF BISNIS SYARIAH - Nabila Rahmadani; Sandra Dewi (CV. Adiba Aisha Amira, 2025)
This research is motivated by the increasingly competitive business competition in the culinary industry, especially the bakery business. In order to win the competition, business actors must pay attention to and apply the right marketing mix. This study aims to identify and analyze the implementation of the marketing mix at Bunda Cake & Bakery Bukittinggi. The purpose of this study is to determine how the marketing mix in facing competition at Bunda Cake & Bakery. This type of research is qualitative research with data collected through observation, interviews and documentation. The analysis technique used is data collection, data reduction, data presentation and drawing conclusions. Based on the results of the study of the four marketing mixes of Bunda Cake & Bakery, the price variable meets the good category, while the product and place variables are classified as medium categories and the promotion variable is classified as low categories. So for the product variable, it needs to be improved again, especially in the indicators of variation, quality, design and packaging. For the place/location variable, it is necessary to expand product distribution so that it can be more easily reached by consumers. The promotion variable needs to be improved again by using social media to expand market reach. From the results of the analysis conducted, in general the marketing mix applied according to the Islamic marketing concept is halal and thayyib products, flexible pricing and always maintaining the cleanliness of the place.